Effectiveness of Make A Match Learning Model on Mathematic Outcome in Elementary School - Zuliana, Zuliana; Rahman, Ithafur (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
This study aims to determine how effective the make a match learning model is on the learning outcomes of mathematics on spatial geometry material for fifth grade students of SD Islam Al Azhar 22 Salatiga. This type of research is quantitative with a pseudo-experimental approach, using a Non-equivalent Pretest-Posttest Control Group design. The data collection technique in this study was by providing tests to assess learning outcomes and documentation as supporting data. The results of this study indicate that the Make a Match learning model has good effectiveness in improving the mathematical understanding of fifth grade students of Al Azhar 22 Salatiga Islamic Elementary School on the material of building spaces. The results of the analysis using the Independent Sample T Test showed a significance value 0.001 which means less than 0.05. Thus, it can be concluded that Ha is accepted and H0 is rejected. In addition, the results of the N-Gain test in the experimental class reached 58.83% which is in the range of 56% - 75% included in the fairly effective category. Based on these results, it can be concluded that the use of the make a match learning model has a fairly effective impact on the learning outcomes of mathematics in spatial geometry material for fifth grade students of SD Islam Al Azhar 22 Salatiga in the 2024/2025 academic year.